Classical Works on Islamic Political Order: Critical Evaluation of the Methodology of the Modern Scholars - Sadia Tabassum (Journal of Islamic and Religious Studies, 2018)
As Muslim scholarship generally treated with the issues relating to rebellion in the manuals of creed, Western scholars and many modern Muslim scholars generally overlooked them. Moreover, when some of them focused on manuals of law-proper where the rules for regulating the conduct of hostilities during rebellion are elaborated, they pick and choose between the views of the jurists belonging to various schools presuming that jurists of various schools followed a common legal theory. The present paper after critically evaluating the methodology of these scholars concludes that every school of law represents a distinct and internally coherent legal theory and as scuh mixing the views of the various schools leads to analytical inconsistency. Hence, it suggests that scholars woking on the legality of rebellion from the perspective of Islamic law should focus on proper legal sources and should adopt a principle-based approach instead of mixing the views of the various schools which are founded on different, sometimes, conficting legal principles.